Adaptive growth strategies of Quercus dentata to drought and nitrogen enrichment: a physiological and biochemical perspective - Zhao, Zipeng; Xie, Bing; Wang, Xiaona; Wang, Qi; Guo, Chang; Zhang, Fang; Wang, Hongru; Zhang, Ruijie; Zhang, Chen (Frontiers in Plant Science, 2024)
Nitrogen deposition and drought significantly influence plant growth and soil physicochemical properties. This study investigates the effects of nitrogen deposition and water stress on the growth and physiological responses of Quercus dentata, and how these factors interact to influence the overall productivity. Two-year-old potted seedlings were selected to simulate nitrogen deposition and water stress. Nitrogen was applied at rates of 0 kg•ha -1 •year -1 (N0) and 150 kg•ha -1 •year -1 (N150).The levels of water stress corresponded to 80% (W80), 50% (W50), and 20% (W20) of soil saturation moisture content. High nitrogen (N150) significantly increased stem elongation and stem diameter by enhancing photosynthetic parameters, including Pn (W80) and Gs (W50), and maintained higher water use efficiency. Under drought conditions, nitrogen enhanced leaf water content, stabilized electrical conductivity, regulated antioxidant enzyme activity, and increased the accumulation of proline. However, under severe drought, nitrogen did not significantly improve biomass, highlighting the critical role of water availability. Additionally, increased nitrogen levels enhanced soil enzyme activity, facilitated the uptake of crucial nutrients like K and Zn. Mantel tests indicated significant correlations between soil enzyme activity, water use efficiency, and leaf Fe content, suggesting that nitrogen deposition altered nutrient uptake strategies in Q. dentata to sustain normal photosynthetic capacity under water stress. This study demonstrates that nitrogen deposition substantially enhances the growth and physiological resilience of Q. dentata under W50 by optimizing photosynthetic efficiency, water use efficiency, and nutrient uptake. However, the efficacy of nitrogen is highly dependent on water availability, highlighting the necessity of integrated nutrient and water management for plant growth.